Emma Thompson: capstone - Thompson, Emma, artist (Colorado State University. Libraries, 2023)
The artist's statement: Clay, as a material, holds embodied memory, recording stories of human touch and identity. The process of working with wet clay is intimate, meditative, and ritualistic. The act of shaping and modeling and carving, the labor of creation, is in many ways more essential to me than the finished piece. Sketching with my hands, finding the piece through the clay itself rather than forcing it into a predetermined direction, I find a rhythm that grounds me in the moment. In this place the shaping of each piece feels like breathing: something my body knows without having to think about it. My hands are my primary tool and through touch I find a conversation with the material. Exploring forms of the female body and of the earth’s body, which shift and morph to become one another, I explore questions of embodiment and identity, that are both personal and universal. Embodied memory is carried through the physicality of the clay, recording the ephemeral moment of touch in permanence. Drawn to the female body and evocations of female identity, I look across human history to find how my individual identity has been shaped along universal currents. What does it mean to reduce a female body to a series of shapes, with complex meanings and symbolism? What does it mean to fragment her, pull her apart, show only pieces of her body? How, in doing this, does she take up space? My process of creating bodies and objects of the body is intimate, healing, and reconnects me to my own body as safe, worthy, beautiful, enough. In creating pieces out of clay, the oldest form of human artwork and domesticity, I allow both the work and myself to occupy space. The body of the earth shares patterns and forms with the human body and becomes inextricable; through making, I find an intimate connection as I see myself as part of this larger body.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery